2014
DOI: 10.1002/acn3.121
|View full text |Cite
|
Sign up to set email alerts
|

Systemic chemotherapy decreases brain glucose metabolism

Abstract: ObjectiveCancer patients may experience neurologic adverse effects, such as alterations in neurocognitive function, as a consequence of chemotherapy. The mechanisms underlying such neurotoxic syndromes remain poorly understood. We here describe the temporal and regional effects of systemically administered platinum-based chemotherapy on glucose metabolism in the brain of cancer patients.MethodsUsing sequential FDG-PET/CT imaging prior to and after administration of chemotherapy, we retrospectively characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…1) [3]. In line with these findings in a recent paper by Sorokin et al [4], we reported a significant decline in global brain function as measured by the degree of FDG uptake following chemotherapy.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…1) [3]. In line with these findings in a recent paper by Sorokin et al [4], we reported a significant decline in global brain function as measured by the degree of FDG uptake following chemotherapy.…”
supporting
confidence: 90%
“…Regional semiquantitative indices showed decreased glucose metabolic function in almost all brain areas (SUV max declines vary from 9 to 24 % and SUV mean declines vary from 6 to 26 % in different areas). Comparing baseline to posttreatment images, they found a mean overall decrease of 22 % (SUV mean ) in glucose metabolism in the gray matter and also significant reduction of metabolism in the white matter and germinal zones [3].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Horky et al found decreased glucose metabolism in both gray and white matter structures associated with chemotherapy for SCLC, and the frontal cortex was more affected (11). In breast cancer patients, Silverman et al used a combination of 15 O-water and 18 F-FDG PET to reveal changes in the activity of the frontal cortex 5-10 y after completion of chemotherapy (12).…”
Section: Discussionmentioning
confidence: 99%
“…Neurotoxicity and its associated cognitive manifestations are poorly characterized, dose‐limiting side effects of chemotherapy treatment . Clinically, the impact of chemotherapy on cognition has been most extensively studied in breast cancer patients, however it is becoming increasingly recognized that cognitive symptoms affect a large portion of patients with varying malignancies and treatments . Despite its prevalence, cognitive dysfunction, often referred to as chemobrain, remains an under‐reported and ill‐defined complication of anti‐cancer treatment.…”
mentioning
confidence: 99%